Strategi Pengembangan Usaha Pada Toko Ikan Tenggiri Eman Carman Dengan Pendekatan Business Model Canvas dan Analisis SWOT - Firdaus, Muhammad Fajar; Herlina, Listri; Kusumawardani, Astrin (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study explores the business development strategy for Toko Ikan Tenggiri Eman Carman using the Business Model Canvas (BMC) framework and SWOT analysis. Traditional operations in the mackerel fish market face challenges such as fluctuating sales and dependency on fixed customer bases and suppliers. These issues result in financial instability and limited market reach. Applying the BMC framework analyzes nine essential components, including customer segments, key partnerships, value propositions, and cost structures. The SWOT analysis identifies internal strengths, weaknesses, and external opportunities and threats, providing a strategic roadmap for business development. This study highlights the need for digital transformation, such as utilizing social media and e-commerce platforms, to diversify sales channels and reduce reliance on traditional markets. Additionally, strategic partnerships with suppliers can stabilize costs and ensure product availability. Implementing these strategies aims to enhance business resilience, expand market access, and secure long-term sustainability. The practical implications of this research provide insights for small-scale business owners, particularly those relying on traditional markets, on how to adapt technology and digital marketing strategies to strengthen their position in an increasingly competitive market. By adopting these strategic steps, Toko Ikan Tenggiri Eman Carman can increase its competitiveness and achieve sustainable growth